Inhibition of the Transforming Growth Factor-β Signaling Pathway Confers Neuroprotective Effects on Beta-Amyloid-Induced Direct Neurotoxicity and Microglia-Mediated Neuroinflammation - Shao Qin Tiong; Raxshanaa N. Mohgan; Jia Yee Quek; Jennifer Yue Suan Liew; Grace Yee Seen Wong; Zi Qing Thang; Zhi Ling Chan; Sook Yee Gan; Elaine Wan Ling Chan (Neurology Research International)
Conclusion: The inhibition of the TGF-β signaling pathway in neuronal and microglia cells by TGF-βR1 inhibitors resulted in neuroprotection against Aβ-induced direct neurotoxicity and microglia-mediated neuroinflammation. Hence, targeting the TGF-β signaling pathway in both neuronal and microglia cells could provide a promising therapeutic strategy in AD.